HUBUNGAN PENGETAHUAN DAN PENDIDIKAN IBU NIFAS TERHADAP PEMILIHAN KONTRASEPSI IUD DI RSUD BANYUMAS - Elok Isti; Prasanti Adriani (Viva Medika, 2011)
The growth of the total population in Indonesia is increasing beyond thecarrying capacity of the growth of life available. Based on the preliminary studyin Banyumas General Hospital from January to December 2010 KB is obtainedfrom 393 participants, who use an IUD 210 (41.58%), after an interview on 21March 2010 to 4 postpartum mothers who use an IUD their average basiceducation (elementary / junior high school), from the 4th respondent answeredthree people do not know about the IUD, while one person answered alreadyknow about the IUD. To examine the relationship of knowledge and education postpartummother against IUD in Banyumas General Hospital in 2010.Methods: This study was descriptive correlation with cross sectional approach, thesample used is accidental sampling, 30 postpartum mother who was in hospitalwhen investigators Banyumas data collection.Results: 30 respondents showed, mother knowledge about the IUD is pretty muchas 23 respondents (76.7%), basic education levels as many as 22 respondents(73.4%), do not choose a contraceptive IUD as many as 17 respondents (56.7 %) The results of Chi-Square test is known there is no relationship ofknowledge about contraceptive IUD puerperal women with contraceptive IUD (p= 0.246> Î± = 0.05). which means that Ho is accepted and Ha rejected. There is norelation between education and puerperal women with contraceptive IUD (p =0.719> Î± = 0.05) means Ho rejected and Ha accepted Keywords: Knowledge, education and contraceptive IUD